The Dynamics Of Sociopolitical Polarization: In-Depth Analysis Of Causes, Consequences, And Mitigation Strategies - Ashariana; Suacana, I Wayan Gede; Dahurandi, Keristian; Hermansyah, Muhammad; Hendarto, Totok (GoAcademica Research & Publishing, 2024)
Sociopolitical polarization is a global phenomenon that affects the stability and cohesion of society, exacerbated by economic inequality, the role of the media, social identity, and the dynamics of international politics. Its impact on democracy, security, public policy, and economic growth creates an urgent need for deeper understanding and effective mitigation strategies. This research aims to analyze the causes, and consequences, and identify mitigation strategies for Sociopolitical polarization. The research was carried out using a descriptive qualitative approach, relying on data from relevant previous studies to process and analyze the phenomenon comprehensively. The results of the research show that Sociopolitical polarization is caused by various interrelated factors and has a broad impact on the social and political structure of society. Effective mitigation strategies include education and media literacy, dialogue and reconciliation, changes in political policies and practices, and regulation of technology and media. However, significant challenges such as resistance to change, the complexity of social identities, and global dynamics require a holistic and sustainable approach. Building consensus in a polarized society and creating a more integrated society is key to overcoming polarization. This research offers valuable insights for stakeholders in designing more effective strategies for reducing Sociopolitical polarization.